Species identification and mitochondrial genomes of ancient fish bones from the Riverine Kachemak tradition of the Kenai Peninsula, Alaska - de Flamingh, Alida (Mitochondrial DNA B Resour, 2018)
Seven fish vertebrae were chosen for analysis from the 49-KEN-147 archaeological site in the Kenai Peninsula, Alaska. Mitochondrial DNA analysis of the ancient fish bones revealed that they were from sockeye and coho salmon. Here, we report the ancient mitochondrial genomes for three sockeye salmon and one coho salmon fish bone.